PREACHING TO GOD, THE CHURCH, AND THE POWERS ACCORDING TO CHARLES L. CAMPBELL: AN IMPERIAL READING ON THE LETTERS OF COLOSSIAN AND EPHESIANS - Junifrius Gultom (Diegesis : Jurnal Teologi, 2023)
This paper explores the issue of preaching to God, the Church, and the powers presented by Charles L. Campbell, where we learn that reading and interpreting Colossians and Ephesians (and indeed the whole New Testament) through the lens of Empire opens up the depths of interpretation and understanding which is not obvious, otherwise. What the New Testament writers penned spoke to the world around them, including the visual cues (art, temples, monuments, coins, festivals), values, politics, economics, faith (especially Emperor cult worship), and the realities of daily life within the Roman Empire. The New Testament writers understood the existence of the three powers (God, the Church, and the spirits or powers). Their daily lives were shaped by all kinds of forces that befall them, and the reality of these forces permeates their writing. The ultimate purpose is we are invited to examine (discern), enumerate, and speak loudly against the rulers, spirits in the air, and the governments of injustice that rule in this world with the power of the one ruler, the Way, which has another Kingdom overcoming the imperial Empire.